2011
DOI: 10.1021/ma201929q
|View full text |Cite
|
Sign up to set email alerts
|

A Particle Tracking Velocimetric Study of Interfacial Slip at Polymer–Polymer Interfaces

Abstract: Particle tracking velocimetry (PTV) was used in conjunction with rheological measurements to investigate slip at polymer–polymer interfaces during and after startup shear using simple shear geometry, i.e., a sliding plate rheometer. Polymer pairs include styrene butadiene rubber (SBR) and polyisoprene (PI) of narrow molecular weight distribution, as well as a PI and polydimethylsiloxane (PDMS), with Flory interaction parameter χ ≈ 0.001 and χ ≈ 0.08 respectively. During startup shear, the SBR-PI pair was able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, for the interphase with entanglement deficiency, in analogy to the PMMA-DMF solutions, the entanglements are very likely to be completely destroyed upon extremely large shears without any re-emergence thereafter, as shown in γ 0 = 3.05 (Figureb). This is in a good accordance with the work of Zartman and Wang, which reported a limitation of interfacial failure at small and intermediate deformations with the broken interface being able to reheal and to sustain the residual shear stress during the last stage of the relaxation whereas at a very large deformation the interphase failed to sustain the imposed stress, as for the interface at an unhealed bilayer.…”
Section: Resultssupporting
confidence: 92%
“…However, for the interphase with entanglement deficiency, in analogy to the PMMA-DMF solutions, the entanglements are very likely to be completely destroyed upon extremely large shears without any re-emergence thereafter, as shown in γ 0 = 3.05 (Figureb). This is in a good accordance with the work of Zartman and Wang, which reported a limitation of interfacial failure at small and intermediate deformations with the broken interface being able to reheal and to sustain the residual shear stress during the last stage of the relaxation whereas at a very large deformation the interphase failed to sustain the imposed stress, as for the interface at an unhealed bilayer.…”
Section: Resultssupporting
confidence: 92%
“…For all calculations, the chain fraction f i = N i /N is assumed to be equal to the volume fraction and N is used to estimate the interaction parameter, χ ij N. ABC miktoarm polymer melts are reported to change morphologies over a narrow range of volume fractions, especially around symmetric composition, which justifies the choice of volume fraction for modeling the system. 29,31 The pairwise interaction parameters were obtained from the studies reported in the literature: χ DM is reported to be ∼0.19 at 150 °C, the annealing temperature used in our work, 12 χ IM is reported to be ∼0.08 at 50 °C69 (assumed to be the same at 150 °C here), and χ ID is reported to be ∼0.08 based on solubility parameter estimation 70 but was found to better fit our observations if a value of 0.0754 was used. Zone annealing was used to equilibrate the system.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…ABC miktoarm polymer melts are reported to change morphologies over a narrow range of volume fractions,especially around symmetric composition, which justifies the choice of volume fraction for modeling the system 29,31. The pairwise interaction parameters were obtained from the studies reported in literature: χDM is reported to be ~ 0.19 at 150 °C, the annealing temperature used in our work,12 χIM it is reported to be ~ 0.08 at 50 °C 69 (assumed to be the same at 150 °C here) and χID is reported to be ~ 0.08 based on solubility parameter estimation,70 but was found to better fit our observations if a value of 0.0554 was used. If a χID value of 0.08 is chosen instead of 0.0554 then[4.8.8] tiling pattern tends to have lower free energy than the experimentally observed [6.6.6] tiling.…”
mentioning
confidence: 87%
“…Several experiments on steady shear flows of multilayer and bilayer films have quantified the relationship between applied shear stress and the velocity of interfacial slip along a single interface. The results show that slip is a strongly nonlinear phenomena. A nonzero slip velocity is detectable above a threshold shear stress that is set by experimental limits and increases rapidly (much faster than linearly) with increasing stress beyond this threshold.…”
Section: Introductionmentioning
confidence: 99%